Penilaian Kualitas Layanan di BPSDMP Kominfo Surabaya dengan Metode Service Quality dan Importance Perfomance Analysis (Studi Kasus Pelatihan Digital) - Adriansyah, Gusti; Ardhyani, Ika Widya; Herlambang, Ichtiar Bagus (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2025)
In government agencies, especially in the field of human resource development which provides community facilities and services, the quality of the services provided must be taken seriously. The quality of this service has a big influence on government agencies, especially in the field of human resource development. This research takes a case study at BPSDMP Kominfo Surabaya regarding service quality assessment using the Service Quality and Importance Performance Analysis methods. The aim is to find out people's expectations and perceptions based on services attribute on digital training. The service quality of BPSDMP Kominfo Surabaya has an average value of 1.43, where the value is close to 1, which indicates that the service provided by the agency has met customer expectations and indicates good service quality. Corrective steps for attributes that do not meet customer expectations include improving the attitude and behavior of the committee, improving the quality of materials and training modules on a regular basis, and ensuring that the food provided is fresh and not stale by re-checking its availability and quality.